(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the expression of quantitativeness in Uzbek and English, focusing on linguistic tools and their application. A detailed analysis of quantitativeness at phonetic, morphological, lexical, and phraseological levels has been conducted. The study examines how quantitativeness, originally a concept in exact sciences such as mathematics and physics, is applied in linguistics through various grammatical means. The use of specific grammatical and lexical units, including numerals, numeratives, and quantifiers, is analyzed. In Uzbek, quantitativeness is expressed through counting words and specific lexical units, while in English, quantifiers are used with countable and uncountable nouns. The results of the research highlight the scientific importance of quantitativeness in linguistics, showcasing its potential for precise and vague expression of quantitative indicators in linguistic units. Additionally, the study identifies commonalities and differences in the representation of quantitativeness in Uzbek and English based on linguistic analysis. This article serves as a theoretical and practical foundation for studying quantitativeness at various linguistic levels.